Correlations between Physical Activity Level, Quality of Life, and Cognitive Performance in Elderly Individuals Engaging in Multi-Year Dance Activities. Issue 1 (March 2022) - Tommasini, Ester; Cipriani, Eleonora; Antonietti, Alessandro; Galvani, Christel
Introduction: It is well-acknowledged that cognitive and physical decline associated with aging can be prevented or reduced with the engagement in regular physical activity (PA). Dance activities combine cardiovascular, cognitive, and coordinative demands, providing a popular leisure PA among elderly. Tis study examined the correlations between quality of life (QoL), cognitive and physical performance, and PA level in older adults who participated in at least 10 years of amateur ballroom dancing. Methods: The study was designed as an observational study. A sample of 20 (10 men; age range: 65 to 80 years; BMI: 26.3 ± 3.0 kg/m 2 ) amateur senior dancers were compared with a sample of 18 (8 men; age range: 65 to 75 years; BMI: 25.5 ± 2.4 kg/m 2 ) non-sedentary individuals (control group) following an adapted PA program. Quality of life and cognitive functioning assessment tools were administered: 36 Health Status Survey (SF-36v2), Montreal Cognitive Assessment (MoCA), and Cognitive Reserve Index questionnaire (CRIq). Physical performance was measured with their preferred walking speed (PWS), and level of moderate to vigorous physical activity (MVPA) was evaluated using a multi-sensor activity monitor. Results: Participants presented a good SF-36v2 physical component and a very good mental component summary, a total MoCA score within the limits, and an average total CRIq score. Their PWS and daily MVPA were high. Differences neither in the three questionnaires nor in PWS and PA level were observed between groups. A significant, moderate, and positive correlation was found between PWS and SF-36v2 physical component summary score. Conclusion: Ballroom dancing seems to allow elderly individuals to maintain good cognitive and physical abilities, QoL, an acceptable normal cognitive reserve, notable physical performance, and PA level to the same extent as an adapted PA program. Both types of PA seem to be able to contrast the mental and physical decline associated with aging.